Formative research to understand food beliefs and practices relating to pregnancy on Kei Besar Island, Eastern Indonesia - Jessica Gloria Mogi; M Premikha; Ona Nabila; Adhi Sanjaya; Indira Prihartono; Joel Gittelsohn (BMC Nutrition, 2024)
Abstract Background Food-related beliefs and practices during pregnancy may contribute to the high prevalence of chronic energy deficiencies (CED) in Eastern Indonesia, particularly in Southeast Maluku regency, where 21.33% of pregnant women experience CED. Currently, little information on these issues is available. This study investigates food beliefs and practices related to pregnancy on Kei Besar Island in the Maluku province of Eastern Indonesia. Methods A qualitative study was conducted utilizing in-depth interviews, free lists, and pile sort exercises. Data collection was conducted in January 2023 and involved married pregnant women aged 18 and above (n = 12), community health volunteers (n = 2), and traditional healers (n = 3) from 9 villages in Kei Besar District. All participants must be natives of Kei Besar Island, with community health volunteers and traditional healers being respective figures recommended by the local villagers. Results The need to avoid or minimize consumption of certain foods during pregnancy, such as some kinds of fish, chili and spicy food, soda, pineapples, octopus, squid, and ice was reported by more than one-third of all participants. Consumption of prescribed foods, such as cassava leaves, papaya, coconut water, rice during early pregnancies, moringa leaves, bananas, and katok leaves was reported by five or more participants. These food proscriptions and prescriptions were due to concerns about the risks of miscarriage, adverse effects on the fetus and mother, and complications during labor. Participants also reported other practices, such as eating for two during early pregnancy and reducing food intake in late pregnancy. We found that food beliefs have shaped the dietary patterns of most participants. However, they still consumed food recommended by community health volunteers and midwives. Conclusions Food beliefs are present and practiced in the Kei Besar community and may impact the nutritional status of women and their infants. Interventions should target training healthcare providers and community health volunteers to provide culturally appropriate health education that incorporates prescribed local ingredients and provides nutritionally adequate substitutes for the proscribed food items. Trial Registration Not applicable.